Targeted disruption of gp130, a common signal transducer for the interleukin 6 family of cytokines, leads to myocardial and hematological disorders. - Yoshida, K (1996)
gp130 is a ubiquitously expressed signal-transducing receptor component shared by interleukin 6, interleukin 11, leukemia inhibitory factor, oncostatin M, ciliary neurotrophic factor, and cardiotrophin 1. To investigate physiological roles of gp130 and to examine pathological consequences of a lack of gp130, mice deficient for gp130 have been prepared. Embryos homozygous for the gp130 mutation progressively die between 12.5 days postcoitum and term. On 16.5 days postcoitum and later, they show hypoplastic ventricular myocardium without septal and trabecular defect. The subcellular ultrastructures in gp130-/- cardiomyocytes appear normal. The mutant embryos have greatly reduced numbers of pluripotential and committed hematopoietic progenitors in the liver and differentiated lineages such as T cells in the thymus. Some gp130-/- embryos show anemia due to impaired development of erythroid lineage cells. These results indicate that gp130 plays a crucial role in myocardial development and hematopoiesis during embryogenesis.